2019
DOI: 10.1128/mbio.01557-19
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis and Ecological Relevance of Caulobacter Cell Filamentation in Freshwater Habitats

Abstract: All living cells are characterized by certain cell shapes and sizes. Many bacteria can change these properties depending on the growth conditions. The underlying mechanisms and the ecological relevance of changing cell shape and size remain unclear in most cases. One bacterium that undergoes extensive shape-shifting in response to changing growth conditions is the freshwater bacterium Caulobacter crescentus. When incubated for an extended time in stationary phase, a subpopulation of C. crescentus forms viable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 64 publications
2
37
0
Order By: Relevance
“…We observed similar effects of pH on cell area in E. coli strain W3110 and in the evolutionary distant Gram-positive coccus Staphylococcus aureus (SI Appendix, Figure S3). Likewise, during this work two separate studies noted the size of Streptococcus pneumoniae and C. crescentus also increases during growth in alkaline media [23]. Altogether, these findings establish environmental pH as mediator of size across evolutionary distant bacterial species.…”
Section: Resultssupporting
confidence: 71%
“…We observed similar effects of pH on cell area in E. coli strain W3110 and in the evolutionary distant Gram-positive coccus Staphylococcus aureus (SI Appendix, Figure S3). Likewise, during this work two separate studies noted the size of Streptococcus pneumoniae and C. crescentus also increases during growth in alkaline media [23]. Altogether, these findings establish environmental pH as mediator of size across evolutionary distant bacterial species.…”
Section: Resultssupporting
confidence: 71%
“…The average volume of S. aureus cells was reduced by~48% during growth in acidic (pH 5.5) medium compared to alkaline (pH 8.0) medium (average volume of 1.02 ± 0.03 compared to 2.10 ± 0.17 μm 3 ). Likewise, during this work two separate studies noted the size of Streptococcus pneumoniae and C. crescentus also increases during growth in alkaline medium [25,26]. Altogether, these findings establish environmental pH as a mediator of size across evolutionarily distant bacterial species.…”
Section: Ph Influences Cell Size In Diverse Bacteriasupporting
confidence: 73%
“…That is, S. elongatus may use temperature as a cue to elongate so as to avoid planktivorous protists. Consistent with this possibility, previous studies have demonstrated that several freshwater bacteria, including Caulobacter crescentus (58), exhibit high phenotypic plasticity and can transition to a filamentous morphology -a transition that may be specifically triggered in the presence of a size-selective protistan predator (63,65,66). It is possible that some aquatic bacteria have evolved to undergo filamentation at temperatures that coincide with grazing season.…”
Section: Cell Division Arrest Filamentation and Asymmetric Cell DIVmentioning
confidence: 70%
“…We propose colder temperatures trigger filamentation indirectly as a carbon-limitation response due to the reduced carbon-fixing activity of RuBisCO. Alternatively, transition into a filamentous morphology has been proposed to confer advantages, such as avoiding phagocytosis via the host immune response (54,55,57,61) or to protect against predation in aquatic environments (58,(62)(63)(64). It is attractive to speculate that the growth temperature of 20 o C coincides with the seasonal temperature during which predation occurs (63).…”
Section: Cell Division Arrest Filamentation and Asymmetric Cell DIVmentioning
confidence: 99%